ANALYSIS OF CAPITAL STRUCTURE AND PROFITABILITY OF STOCK PRICE IN MANUFACTURING COMPANIES ON THE INDONESIAN STOCK EXCHANGE - Mega Selvi; Syahril Efendi (SEAN Institute, 2023)
The aims of this studies were analyze and determining the effects of Capital Structure & Profitability on stock prices in pharmaceutical companies on the IDX. In its measurement, the Capital Structure variable uses the Debt to Equity Ratio (DER) and Profitability uses Return On Assets (ROA) and Share Prices use Price Book Value (PBV) calculations. This research used quantitative technique. The research sample used was 5 companies with the 2015-2021 period (7 research periods). Determined the sample of this study is 35 samples. Based on the results of hypothesis testing, by partially the DER has a positive and significant effect on PBV. But ROA has no positive and insignificant effect on PBV. Meanwhile, simultaneously, DER and ROA have a positive and significant effect on PBV.